Fractional erbium-doped yttrium aluminum garnet laser-assisted drug delivery of hydroquinone in the treatment of melasma - Badawi AM; Osman MA (Dove Medical Press, 2018)
Ashraf M Badawi,1–4 Mai Abdelraouf Osman1 1Dermatology Unit, Department of Medical Applications of Lasers (MAL), National Institute of Laser Enhanced Sciences (N.I.L.E.S.), Cairo University, Giza, Egypt; 2Dermatology and Laser Applications, Szeged University, Szeged, Hungary; 3European Society for Lasers and Energy Based Devices, Strasbourg, France; 4European Society for Cosmetic and Aesthetic Dermatology, Paris, France Background: Melasma is a difficult-to-treat hyperpigmentary disorder. Ablative fractional laser (AFL)-assisted delivery of topically applied drugs to varied targets in the skin has been an area of ongoing study and research.Objective: The objective of this study was to evaluate the efficacy and safety of fractional erbium-doped yttrium aluminum garnet (Er:YAG) laser as an assisted drug delivery for enhancing topical hydroquinone (HQ) permeation into the skin of melasma patients.Patients and methods: Thirty female patients with bilateral melasma were randomly treated in a split-face controlled manner with a fractional Er:YAG laser followed by 4% HQ cream on one side and 4% HQ cream alone on the other side. All patients received six laser sessions with a 2-week interval. The efficacy of treatments was determined through photographs, dermoscopic photomicrographs and Melasma Area Severity Index (MASI) score, all performed at baseline and at 12 weeks of starting therapy. The patient’s level of satisfaction was also recorded.Results: Er:YAG laser + HQ showed significantly better results (p<0.005) with regard to decrease in the degree of pigmentation as assessed on the 4-point scale than HQ alone. There was a significant decrease in MASI scores on Er:YAG laser + HQ side vs HQ side. Minor reversible side effects were observed on both sides.Conclusion: AFL-assisted delivery of HQ is a safe and effective method for the treatment of melasma. Keywords: MASI score, dermoscopy, physician global assessment